Individual Prognosis Regarding Effectiveness of a Therapeutic Intervention Using Pre-Therapeutic “Kinesiology Muscle Test” - Ingrid Waxenegger; P. Christian Endler; Beatrix Wulkersdorfer; Heinz Spranger (The Scientific World Journal)
Since a therapy's full positive effect and possible adverse effects are individual and not predictable for every single patient, scientists have been searching for methods to predict optimal effects of a therapy. This pilot study investigated the applicability of the “kinesiology muscle test” as a prognostic tool regarding effectiveness in a defined therapeutic procedure. Each of 11 test persons with elevated total cholesterol values received a naturopathic drug supposed to lower cholesterol level on a daily basis for eight consecutive weeks. Prior to treatment the “kinesiology muscle test” was performed, where the patient's ability to maintain a flexed position in a selected joint was evaluated. The resistance created by the patient against the tester's pressure was monitored. Being in touch with healthful or unhealthful chemical substances may, according to the kinesiology literature, increase or decrease this resistance. For testing purposes, the drug was placed onto the patients' skin. The ability of the brachioradial muscle to resist the tester's pressure was determined on a subjective scale (0-100%). The Pearson product-moment correlation coefficient between four variables (total cholesterol value before therapy, total cholesterol value after therapy, difference of total cholesterol values before and after therapy, prior to treatment kinesiology testing) was chosen. A significant correlation between the difference of total cholesterol values before-after and the prior to treatment test was found, as well as a significant correlation between the total cholesterol values after therapy and the prior to treatment kinesiology test.